Desenvolvimento de sistema carreador de cartogenina e sinvastatina para engenharia tecidual osteocondral: um modelo in vitro direcionado à osteoartrite - Estrella, Marco Antonio Molina (2025)
Osteoarthritis (OA) is a complex, multifactorial joint pathology with high incidence. Changes in the subchondral bone and cartilage are induced by inflammatory, metabolic, and biomechanical factors, leading to pain and joint dysfunction. In vitro models of human origin that mimic either normal or pathological tissue are sought to advance research in this field. In this sense, this study focused on developing a tissue model of the articular surface, represented by osteochondral tissue. For this, liposomal systems were developed for the delivery of kartogenin (KGN) and simvastatin (SIM), aiming to optimize their bioavailability and differentiation effects. These liposomal systems were incorporated into a hyaluronic acid (HA) gel to enhance the differentiation action. The liposomes containing KGN or SIM were produced by thin-film hydration. The KGN liposomes exhibited an average size of 85.51 ± 0.83 nm, a polydispersity index (PDI) of 0.081 ± 0.004, and a zeta potential of -38.62 ± 0.39 mV, while the SIM-containing liposomes had an average size of 189.09 ± 2.49 nm, PDI of 0.183 ± 0.008, and a zeta potential of -33.86 ± 0.60 mV, showing uniformity and initial stability associated with electrostatic repulsion between the particles. The rheology of the HA hydrogel was analyzed, and a concentration of 20 mg/mL was selected to incorporate the liposomes. To create the osteochondral model, the differentiation of human Mesenchymal Stem Cells (MSCs) was evaluated by immunocytochemistry and confocal microscopy, using anti-SOX9 antibodies for chondrocytes and anti-osteopontin (OPN) antibodies for osteoblasts. The results indicated that liposomes loaded with KGN in HA induced chondrogenic differentiation of MSCs, evidenced by SOX9 expression, while liposomes loaded with SIM stimulated osteogenic differentiation, confirmed by the detection of OPN. This study contributes to recreating the characteristics of cartilage and bone tissues from synovial joints, offering new perspectives for the development of regenerative strategies in the treatment of OA